2011
DOI: 10.1111/j.1744-7909.2011.01056.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Genetic Analysis of a Light‐ and Temperature‐sensitive Spotted‐leaf Mutant in Rice

Abstract: A rice spotted-leaf mutant was isolated from an ethane methyl sulfonate (EMS) -induced IR64 mutant bank. The mutant, designated as spl30 (spotted-leaf30), displayed normal green leaf color under shade but exhibited red-brown lesions under natural summer field conditions. Initiation of the lesions was induced by light and the symptom was enhanced at 33 (°) C relative to 26 (°) C. Histochemical staining did not show cell death around the red-brown lesions. Chlorophyll contents in the mutant were significantly lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 60 publications
(100 reference statements)
0
29
0
Order By: Relevance
“…Environmental factors play an important role in the initiation of leaf lesions in some spl mutants. The spl30 lesions are induced by light, and the severity of the symptom is enhanced by elevated temperatures (Huang et al ). It is generally believed that UV‐light is responsible for the initiation of lesions (Yamanouchi et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental factors play an important role in the initiation of leaf lesions in some spl mutants. The spl30 lesions are induced by light, and the severity of the symptom is enhanced by elevated temperatures (Huang et al ). It is generally believed that UV‐light is responsible for the initiation of lesions (Yamanouchi et al ).…”
Section: Discussionmentioning
confidence: 99%
“…The genetic controls of more than 55 rice spl mutants have been clarified, and a small numbers of genes have been isolated (Kiyosawa ; Yoshimura et al ; Yin et al ; Wu et al ; Chen et al ; Huang et al , ; Babu et al ; Feng et al ). The majority of the spl traits are controlled by single recessive genes, while a few of them are governed by dominant, double‐recessive or maternal genes (Wang et al ; Wu et al ; Huang et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Rice LMMs have been isolated from natural variants or by chemical and physical mutagenesis, and more than 100 rice LMMs have been found to date (Liu et al 2003). Genetic analysis has indicated that the majority of rice LMMs are controlled by single recessive or dominant genes (Wu et al 2008;Huang et al 2010;2011). Seven rice lesion mimic (or spotted leaf) genes have been cloned: Spl7, Spl11, OsLSD1, OsAT1, OsPti1a, Spl28 and SL (Yamanouchi et al 2002;Zeng et al 2004;Wang et al 2005;Mori et al 2007;Takahashi et al 2007;Qiao et al 2010;Fujiwara et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, two spotted leaf genes have been mapped to rice chromosome 3: spl-3 and Spl30 (t) (Yoshimura et al 1997;Huang et al 2011). The spl-3 gene was mapped between RFLP markers XNpb173 and XNpb348 on rice chromosome 3 (Yoshimura et al 1997); according to the Gramene database, spl-3 and bl4 (or lrd9) are the same gene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation